Determination of Selected Heavy Metals Concentration in Soil along the East-West Highway Road Shoulder in front of UMK Jeli Campus, Jeli, Kelantan, Malaysia - Aweng E.R., Chong K.K., Arham Muchtar A.B., Sharifah Aisyah S.O., Liyana A.A., M. Mazlan (International Journal of Advanced Science and Technology, 2020)
Road shoulder receives all pollutants associated with runoff including heavy metals from the moving vehicles on the road. The pollutant will eventually end up in the river nearby or shallow groundwater. Thus, the concentration of heavy metals in the road shoulder soils along the East-West highway in front of UMK Jeli Campus, Kelantan, Malaysia was studied. The main objective of the study was to determine the concentration of selected heavy metals, namely Zn, Pb, Mn, Cd and Cu in the soil at the road shoulder. The soil samples were collected from ten stations along the East-West Highway and analyzed for the concentration of selected heavy metals using Atomic Absorption Spectrophotometer (AAS). To support the findings, a traffic count was conducted. It was found that the average number of vehicles using this road ranged between 1,563 vehicles per day in the morning and 1,819 vehicles per day in theevening.90% of the vehicles were powered by petrol engines. The results show that the mean concentration of Mn was the highest (10.3011 mg/L) and Cd concentration was the lowest (0.0116 mg/L). On the other hand, the mean concentration of Zn was 4.4824 mg/L, Pb was 2.1378 mg/L, and Cu was 0.5608 mg/L. All the mean concentration of heavy metals was higher as compared to the Natural Range of Heavy Metals (NRHM) and Critical Limits for Heavy Metals Concentration (CLHMC) in soil except for Mn. However, there were no significant different (P>0.05) of heavy metals concentration between sampling stations. The values of the heavy metal suggest that vehicle is the main source of heavy metals contamination in the road shoulder soils since there are no other activities in the vicinity. The results of the study provide information on the concentration of heavy metals in the road shoulder that can be used as a basis to develop the Heavy Metal Allowable Limits (MSHMAL) in soil for Malaysia.